PENGARUH INSTITUTIONAL OWNERSHIP TERHADAP FIRM VALUE MELALUI DIVIDEND POLICY PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2015 - Mozes Adiguna Setiyono; Devie Devie Devie (Business Accounting Review, 2017)
This study aims to investigate the affect of institutional ownership to firm value through dividend policy as intervening variable on companies which listed in Indonesia Stock Exchange during 2013-2015. Institutional ownership was measured by percentage of shares owned by institutions. Dividend policy was measured by dividend payout ratio. Firm value was measured by Tobin’s Q. The sample of this research consisted of 100 companies that listed in Indonesia Stock Exchange between the periods of 2013-2015.Data analysis technique used in this study was partial least square to describe the relationship between the variables. The data were processed by using WarpPLS 5.0. The results showed that institutional ownership and dividend policy had positive and significant relationship on firm value of company listed in Indonesia Stock Exchange. The institutional ownership also affected positively and significantly the dividend policy.